Regional Lung Recruitability During Pneumoperitoneum Depends on Chest Wall Elastance – A Mechanical and Computed Tomography Analysis in Rats - Comuzzi, Lucia; de Abreu, Mariana B.; Motta-Ribeiro, Gabriel C.; Okuro, Renata T.; Barboza, Thiago; Carvalho, Niedja; Lucangelo, Umberto; Carvalho, Alysson R.; Zin, Walter A. (Frontiers in Physiology, 2018)
Background: Laparoscopic surgery with pneumoperitoneum increases respiratory system elastance due to the augmented intra-abdominal pressure. We aim to evaluate to which extent positive end-expiratory pressure (PEEP) is able to counteract abdominal hypertension preventing progressive lung collapse and how rib cage elastance influences PEEP effect. Methods: Forty-four Wistar rats were mechanically ventilated and randomly assigned into three groups: control (CTRL), pneumoperitoneum (PPT) and pneumoperitoneum with restricted rib cage (PPT-RC). A pressure-volume (PV) curve followed by a recruitment maneuver and a decremental PEEP trial were performed in all groups. Thereafter, animals were ventilated using PEEP of 3 and 8 cmH2O divided into two subgroups used to evaluate respiratory mechanics or computed tomography images. In 26 rats, we compared respiratory system elastance (Ers) at the 2 PEEP levels. In 18 animals, computed tomography images were acquired to calculate total lung volume (TLV), total volume and air volume in six anatomically delimited regions of interest (3 along the cephalo-caudal and 3 along the ventro-dorsal axes). Results: PEEP of minimal Ers was similar in CTRL and PPT groups (3.8±0.45 and 3.5±3.89 cmH2O, respectively) and differed from PPT-RC group (9.8±0.63 cmH2O). Chest restriction determined a right- and downward shift of the PV curve, increased Ers and diminished TLV and lung aeration. Increasing PEEP augmented TLV in CTRL group (11.8±1.3 to 13.6±2 ml, p<0.05), and relative air content in the apex of PPT group (3.5±1.4 to 4.6±1.4 %TLV, p<0.03) and in the middle zones in PPT-RC group (21.4±1.9 to 25.3±2.1 %TLV cephalo-caudally and 18.1±4.3 to 22.0±3.3 %TLV ventro-dorsally, p<0.005). Conclusions: Regional lung recruitment potential during pneumoperitoneum depends on rib cage elastance, reinforcing the concept of PEEP individualization according to the patient’s condition.